MASIH RELEVANKAH SISTEM NASIONAL INDONESIA PADA ERA PASCA REFORMASI DEWASA INI ? - Kertopati, Ton (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2006)
A well known adage wants that in many social settings it is well to avoid discussing either politics, religion or philosophy presumablyÂ  such conversations generated more heat than light.Political analysis about crucial changes are currently taking place in the political and social-cultural Indonesian life.The challenges lie under the growing influence of globalism and was oriented toward the application of the modelsÂ  in the open society.The text present a tecnigue for thinking logically and also based on conviction whether political inquiry and analysis rely on the use of the Indonesian system of life (Sistem Kehidupan Nasional) still valid A System as Collection of matters within presented boundaries, Empharize: the Open society and democracy based on several applications.